1995
DOI: 10.1002/pro.5560040406
|View full text |Cite
|
Sign up to set email alerts
|

Homology model of human interferon‐α8 and its receptor complex

Abstract: Human interferond (HuIFNa8), a type I interferon (IFN), is a cytokine belonging to the hematopoietic superfamily that includes human growth hormone (HGH). Recent data identified two human type I IFN receptor components. One component (p40) was purified from human urine by its ability to bind to immobilized type I IFN. A second receptor component (IFNAR), consisting of two cytokine receptor-like domains (D200 and D200'), was identified by expression cloning. Murine cells transfected with a gene encoding this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…These results, along with the relatively similar risks associated with susceptibility to SMA for the IFNA8 TA genotype (OR=2.80) and the −173T/−884A (TA) haplotype (OR=3.98), and their comparable reductions in circulating IFN-α, suggests that it is actually variation at IFNA8 −884 that is driving the genetic-based relationship and consequent changes in IFN-α. These results are consistent with previous studies showing that the IFNA8 subtype is one of the most important type 1 interferon subtypes for regulating potent IFN-α production (Foster et al 1996; Garcia et al 2007; Izaguirre et al 2003; Seto et al 1995). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results, along with the relatively similar risks associated with susceptibility to SMA for the IFNA8 TA genotype (OR=2.80) and the −173T/−884A (TA) haplotype (OR=3.98), and their comparable reductions in circulating IFN-α, suggests that it is actually variation at IFNA8 −884 that is driving the genetic-based relationship and consequent changes in IFN-α. These results are consistent with previous studies showing that the IFNA8 subtype is one of the most important type 1 interferon subtypes for regulating potent IFN-α production (Foster et al 1996; Garcia et al 2007; Izaguirre et al 2003; Seto et al 1995). …”
Section: Discussionsupporting
confidence: 93%
“…However, due to post-translational modifications, there are more than 22 IFN-α subtypes differing by one or two amino acids (Bekisz et al 2004; Song et al 2006). Several in vitro studies showed that these subtypes vary considerably in their ability to produce IFN-α in response to viruses and other stimuli (Izaguirre et al 2003; Seto et al 1995). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, increased fluctuation within the receptor-binding interface region of human growth hormone (hGH) was recently linked directly to the increased free energy of the protein-receptor binding (60), which belongs to the same hematopoietic super-family that includes type I interferons (61). The two proteins (hGH and IFN) are highly homologous, so much so that hGH was used in earlier homology modeling of IFN and INF/IFNARs binding (61, 62).…”
Section: Conformational Changes Detected By Hdx Ms: Relevance For Thementioning
confidence: 99%
“…The two proteins (hGH and IFN) are highly homologous, so much so that hGH was used in earlier homology modeling of IFN and INF/IFNARs binding (61, 62). Helix 1 of hGH is noticeably more stable compared to its cousin helix A of IFN; however, introducing a structure-destabilizing mutation in helix 1 leads to a noticeable increase in the receptor binding affinity (60).…”
Section: Conformational Changes Detected By Hdx Ms: Relevance For Thementioning
confidence: 99%